1971
DOI: 10.1139/f71-098
|View full text |Cite
|
Sign up to set email alerts
|

World Distribution of Rainbow Trout (Salmo gairdneri)

Abstract: Since 1874, the endemic range of the rainbow trout, Salmo gairdneri Richardson, has been extended through introduction to include eastern North America and the continents of Africa, Asia, Australasia, Europe, and South America. The present range of the species extends into low latitudes by the use of waters at high elevations to over 4500 m above sea level.Environmental factors considered to be of primary importance in the survival of introduced populations are water temperature and precipitation. The presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
196
0
5

Year Published

1984
1984
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(203 citation statements)
references
References 22 publications
2
196
0
5
Order By: Relevance
“…This observation agrees with MacCrimmon (1971), who reported that the rainbow trout samples introduced in the mountain areas of São Paulo state came from California in the early 1960's. The study of other naturalized populations and the use of alternative molecular markers may lead to a better understanding of the relationships among rainbow trout stocks in Brazil.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This observation agrees with MacCrimmon (1971), who reported that the rainbow trout samples introduced in the mountain areas of São Paulo state came from California in the early 1960's. The study of other naturalized populations and the use of alternative molecular markers may lead to a better understanding of the relationships among rainbow trout stocks in Brazil.…”
Section: Resultssupporting
confidence: 92%
“…In 1962, a large official program was set up, and rainbow trout eggs were imported from California (EUA), in order to start the culture of this species in fish farms, and also to introduce it into some rivers of the Serra da Bocaina (Rio de Janeiro and São Paulo), Serra da Mantiqueira (São Paulo), and other mountain fluvial systems, located in the northern region of the state of Santa Catarina (MacCrimmon, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Surface water temperatures exceeded 25°C in February 1978, and such high temperatures are beyond the point at which trout cease feeding (Embody 1927in MacCrimmon 1971. Furthermore, shag densities increased markedly over this summer period and the trout, limited in distribution by water quality and lacking cover formerly provided by weed beds, would have been further affected by this increased predation pressure.…”
Section: Factors Affecting Trout Distribution and Growth Over Summermentioning
confidence: 99%
“…Rainbow trout (Oncorhynchus mykiss) are very adaptable (MacCrimmon 1971), occurring in their native North America in a range of habitats including rivers, lakes, and the ocean. Introduced into New Zealand in the 1880s (McDowall 1990), rainbow trout are usually associated with lakes where they occur in sympatry with two other introduced salmonids-frequently with the widespread brown trout, and occasionally with populations of lake-limited chinook salmon.…”
Section: Introductionmentioning
confidence: 99%